The correct derivation of the relativstic Doppler effect (International Journal of Scientific Research and Management (IJSRM), 2022)
In the present publication it shall be shown that the derivation of the relativistic Doppler effect is based on the fact that every object at high velocity experiences not only an increase of mass compared to its resting state, but also an increase of frequency of all its oscillating systems. This topic, which has already been treated in source [01], is deepened in the present publication.